MODEL PEMBELAJARAN MASA’IL FIQHIYYAH DI PONDOK MODERN DARUSSALAM GONTOR PUTRI 1 - Syarifah Syarifah; Bintang Alfaradis; Nailin Tasnim Nur Muthmainnah Sihotang (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study examines the implementation of a Masa’il Fiqhiyyah–based learning model as an integrative framework for curriculum development in Islamic boarding school education, focusing on sixth-grade Kulliyatul Mu’allimin al-Islamiyah (KMI) students at Pondok Modern Darussalam Gontor Putri Campus 1. Masa’il Fiqhiyyah is positioned not only as learning content, but also as an analytical learning model that links legal reasoning, ethical values, and practical religious life within the pesantren system. The research employed a descriptive qualitative approach using document analysis. Data were collected from primary and secondary sources, including curriculum documents, instructional guidelines, learning modules, institutional regulations, and relevant academic literature on fiqh education and Islamic curriculum development. The data were analyzed through descriptive-analytical and thematic techniques to identify patterns of integration across intracurricular, co-curricular, and extracurricular learning domains. The findings indicate that Masa’il Fiqhiyyah learning is implemented holistically and systematically. In the intracurricular domain, it is applied through classroom-based case discussions and analytical learning that develop students’ ability to identify legal problems, examine textual evidence, and formulate reasoned legal conclusions. In the co-curricular domain, activities such as fath al-kutub, baḥṡ al-masā’il, and supervised worship practices strengthen understanding and legal argumentation skills while cultivating academic ethics.